Performance Based Seismic Design of Reinforced Concrete Building by Non-linear Static Analysis: Evaluating Seismic Performance of Reinforced Concrete Buildings using Non-linear Static Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recent earthquake disasters in the world have shown that significant damage can occur even when the buildings are designed to satisfy the codal provisions, thus exposing the inability of the codes to ensure minimum safety of the structures under an earthquake. The displacement-based approach known as the performance-based seismic design (PBSD), which evaluates how building systems are likely to perform under a variety of conditions associated with potential hazard events, is becoming very popular now. In contrast to force-based approaches, PBSD provides a systematic methodology for assessing the seismic performance of a building, thus ensuring life safety and minimum economic losses. PBSD demands the use of non-linear analysis procedures to evaluate the response of structures under lateral loads. The non-linear time history analysis is the most accurate, but requires much computational effort, time and cost. Thus, the use of nonlinear static analysis procedure known as the pushover analysis has been proposed. In pushover analysis, the magnitude of the lateral loads is incrementally increased, maintaining a predefined distribution pattern along the height of the building. It gives an insight on the progressive mode of failure of the structure, thus making it more performancebased. The scope of the present study aims at evaluation of RC buildings designed according to IS 4562000. The non-linear static pushover analysis procedure has been used in this regard. The non-linear methods can give an Idea regarding the pattern of the plastic hinge formations and thus aid in the performance based seismic design of the structure. The pushover analysis has been carried out using ETABS Software. The results of analysis have been compared in terms of base shear, storey drift, storey displacements and plastic hinge rotations. An existing five storeyed residential building was analysed for seismic performance using the dual requirement of life safety under design basis earthquake (DBE) and collapse prevention under maximum considered earthquake (MCE).